One- vs. Two-Stage Revision for Periprosthetic Shoulder Infections: A Systematic Review and Meta-Analysis - Mohamad Bdeir; Aimée Lerchl; Svetlana Hetjens; Andreas Schilder; Sascha Gravius; Tobias Baumgärtner; Ali Darwich (MDPI AG, 2024)
Periprosthetic shoulder infection (PSI) remains a challenging complication after shoulder arthroplasty. Therapeutic options include one- or two-stage revision, irrigation and debridement, and resection arthroplasty. With our systematic review and meta-analysis, we aimed to compare one- and two-stage revisions for periprosthetic shoulder joint infections and determine the most appropriate therapeutic procedure. We performed an extensive literature search in PubMed, Ovid Medline, Cochrane Library, Web of Science, and CINAHL and filtered out all relevant studies. The meta-analysis was performed using the random-effects model, heterogeneity was analyzed using I2, and publication bias was assessed using the Egger's test. A total of 8 studies with one-stage revisions, 36 studies with two-stage revisions, and 12 studies with both one-stage and two-stage revisions were included. According to the random-effects model, the reinfection rate for the entirety of the studies was 12.3% (95% Cl: 9.6-15.3), with a low-to-moderate heterogeneity of I2 = 47.72%. The reinfection rate of the one-stage revisions was 10.9%, which was significantly lower than the reinfection rate of the two-stage revisions, which was 12.93% (p = 0.0062). The one-stage revision rate was significantly lower with 1.16 vs. 2.25 revisions in the two-stage revision group (p < 0.0001). The postoperative functional outcome in one-stage-revised patients was comparable but not statistically significant (p = 0.1523). In one- and two-stage revisions, most infections were caused by Cutibacterium acnes. In summary, our systematic review and meta-analysis show the superiority of single-stage revision regarding reinfection and revision rates in periprosthetic shoulder joint infection.